Manajemen Pembelajaran Pondok Pesantren Ash-Shiddiqiyyah dan Al-Hidayat Berjan - Anwar, Sirojul (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2024)
Learning Management at the Ash-Shiddiqiyyah and Al-Hidayat Berjan Islamic Boarding Schools, Gebang District, Purworejo Regency. This research aims to determine the uniqueness of education management in two Islamic boarding schools that have different teachers, but carry out activities together, even though in general different Islamic boarding schools will hold their own learning. In this research, the author used a qualitative method with a field research approach. The data analysis used is using interactive model analysis from Miles and Huberman with data reduction, data presentation and providing conclusions. The results of this research are that these two Islamic boarding schools are two different and independent Islamic boarding schools, it's just that in implementing learning, they still do it together, this is because these two Islamic boarding schools complement each other, Al-Hidayat does not accept male students and Ash-Shiddiqiyyah does not accept female students so it allows them to walk together. Planning, implementation and evaluation are carried out jointly, although at Al-hidayat Islamic Boarding School there are several activities that are carried out independently, apart from that, Al-Hidayat Islamic Boarding School also has a tahfidz program which is not carried out at As-Shiddiqiyyah Islamic Boarding School.